Environmentally Sustainable Transport (EST): Concept, Goal, and Strategy – The OECD’s EST Project - Wiederkehr, Peter; Gilbert, Richard; Crist, Philippe; Caïd, Nadia (European Journal of Transport and Infrastructure Research, 2004)
OECD countries recognized in the mid-1990s that transport trends were not sustainable and that existing policy frameworks seemed unlikely to be able to move society towards more sustainable transport systems. A new approach to transport policy was required that would be consistent with the broad definition of sustainable development. To this end, the project on Environmentally Sustainable Transport (EST) was initiated to give some precision to the concept of EST through the use of criteria that have environmental significance and can be quantified. A method known as ‘backcasting’ was used to develop policies and strategies for achieving a desired future state through targeted action. This paper summarizes the results of the project, which involved twelve OECD countries that undertook case studies at local, regional, national and international scales. The project concluded that some 40 per cent of the effort necessary to meet the EST criteria will come from technology and 60 per cent from demand-side management and a shift towards more sustainable transport modes. EST is attainable, but only if a broad range of instruments is deployed. These include regulations and standards, fiscal measures, changes in governance arrangements, and education, the provision of information, awareness raising, and attitude change, all assembled into coherent packages of instruments applied with careful consideration to phasing.